COMPARISON OF TRAMADOL AND ONDANSETRON IN PREVENTION OF POSTOPERATIVE SHIVERING AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Dr Hira Saeed; Dr Taoseef Ahmed; Dr Ayesha Arshad; Dr Syed Sajjad Raza Kazmi; Muhammed Naeem; Dr Asif Hussain; Dr Nimra Usman (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Shivering as a post-operative complication after laparoscopic cholecystectomy is common which usually manifests itself in increased metabolic demands and discomfort of patients. Proper prevention plays an important part in the increased favorability of the recovery outcomes. Other drugs which have a potential effect in reducing shivering are Tramadol (an opioid analgesic drug) and Ondansetron (a 5HT3 antagonist mainly used for nausea) among others. This comparison of efficacy for postoperative shivering preventing by the two drugs aims at guiding clinicians for the best pharmacologic management for improved patient care and perioperative safety in minimal-invasion surgeries.MethodsThis randomised controlled trial was conducted in the Department of Anaesthesiology, Sir Ganga Ram Hospital, Lahore, over a period of six months, from 1st April to 30th September 2020, following approval of the study protocol. In total, 92 patients who were in the age group 20 to 70 and any gender were randomly assigned to the two study groups. In one group, patients got ondansetron given through IV and in the other group, patients received tramadol the same way for preventing shivering after surgery. Grade II or greater postoperative shivering within 30 minutes of extubation was the major outcome observed. Written consent was provided by all the study participants before they took part in the research.ResultsThe average age among participants was 41.5 years with a standard deviation of 14.3 years. A higher number of females were included in the study, reflected by a male-to-female ratio of 1:2.1. Obesity was identified in 18 patients (19.6%). According to the American Society of Anesthesiologists (ASA) physical status classification, 47 individuals (51.1%) were categorized as class I, and 45 (48.9%) as class II. Postoperative shivering occurred in 20 patients (21.7%) who underwent laparoscopic cholecystectomy under general anesthesia. A significantly lower incidence of shivering was observed in those administered tramadol compared to those given ondansetron (8.7% vs. 34.8%; p = 0.002). This trend remained consistent across different patient subgroups when stratified by age, sex, body mass index, and ASA classification.CONCLUSION: The study has compared the effectiveness of intravenous tramadol and ondansetron in patients who followed general-anesthesia and it was found that tramadol is better than ondansetron in the prevention of postoperative shivering and this difference in effectiveness is seen regardless of age, gender, body mass index and American Society of Anesthesiologists (ASA)groups. These findings are indicative that tramadol can eventually be the agent of choice in preventing shivering in the future practice of anesthesia.